Peranan SDM dalam Meningkatkan Efektifitas Pelayanan PLN melalui Kolaborasi PLN UP3 Nias dengan Masyarakat di Desa Hambawa Kecamatan Gunungsitoli Utara - Meliaman Ndruru; Augustinus Ndruru; Otonius Tafonao; Umi Habibah Hasanah Zebua; Nitra Rusni lince Zebua; Yupiter Mendofa (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2025)
This study aims to analyze the role of human resources (HR) in improving the effectiveness of public services through a collaborative approach between PLN UP3 Nias and the community in Hambawa Village, Gunungsitoli Utara District. The background of this study is based on the importance of HR competencies in supporting responsive, adaptive, and participatory electricity services, especially in 3T areas. Using a qualitative approach through a case study design, data was collected through in-depth interviews, participatory observation, and documentary analysis of PLN's collaborative practices at the village level. The research findings indicate that the collaboration between PLN and the community successfully accelerated the resolution of power outages, reduced the number of customer complaints, and significantly improved community satisfaction. The role of human resources with technical skills, social adaptability, and communication proficiency is a key factor in building synergy with local communities. This study implies that improving the quality of public services in remote areas can be achieved by strengthening human resource capacity that is not only focused on internal efficiency but also on transformative social engagement.